2012
DOI: 10.1080/03079457.2011.631983
|View full text |Cite
|
Sign up to set email alerts
|

Protection induced by commercially available live-attenuated and recombinant viral vector vaccines against infectious laryngotracheitis virus in broiler chickens

Abstract: Viral vector vaccines using fowl poxvirus (FPV) and herpesvirus of turkey (HVT) as vectors and carrying infectious laryngotracheitis virus (ILTV) genes are commercially available to the poultry industry in the USA. Different sectors of the broiler industry have used these vaccines in ovo or subcutaneously, achieving variable results. The objective of the present study was to determine the efficacy of protection induced by viral vector vaccines as compared with live-attenuated ILTV vaccines. The HVT-LT vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 32 publications
8
74
0
1
Order By: Relevance
“…In recent years, recombinant vaccines are available in the market, and include the insertion of ILT viral glycoproteins into viral vectors, such as poxvirus (FPV) (Davison et al, 2006) and turkey herpesvirus (HVT) (Vagnozzi et al, 2012). A recombinant fowl pox vaccine, containing the gene encoding the glycoprotein B (gB), was shown to protect chickens against virulent ILTV strains (Tong et al, 2011).…”
Section: Vaccinationmentioning
confidence: 99%
“…In recent years, recombinant vaccines are available in the market, and include the insertion of ILT viral glycoproteins into viral vectors, such as poxvirus (FPV) (Davison et al, 2006) and turkey herpesvirus (HVT) (Vagnozzi et al, 2012). A recombinant fowl pox vaccine, containing the gene encoding the glycoprotein B (gB), was shown to protect chickens against virulent ILTV strains (Tong et al, 2011).…”
Section: Vaccinationmentioning
confidence: 99%
“…In addition, they can be administered in ovo without a negative impact on production performance (Johnson et al, 2010). Recent studies suggest that although these vaccines reduce clinical signs, they do not reduce challenge virus loads in the trachea as live attenuated vaccines do (Johnson et al, 2010;Vagnozzi et al, 2012). Dark purple regions with a grid pattern indicate countries where ILT cases have been documented for longer than 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally it has been demonstrated that although recombinant viral vectored vaccines do reduce clinical signs of the disease, they fail to prevent viral shedding. On the other hand, live-attenuated vaccines are more efficacious in reducing clinical signs and viral shedding (Johnson, et al, 2010;Vagnozzi et al, 2012a) but can still transmit from vaccinated to non-vaccinated chickens (Rodriguez et al, 2007). It has been speculated that incomplete en mass vaccination, particularly with CEO vaccines, results in long-term persistence of selective vaccine subpopulations (García & Riblet, 2001;García et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…These strains were attenuated by serial passages in either embryonated chicken eggs (chicken embryo origin, CEO) or in chicken tissue culture (tissue culture origin, TCO) (Gelenczei & Marty, 1965;Samberg & Aronovici, 1969). Viral vector vaccines expressing ILTV glycoproteins in turkey herpesvirus (HVT) and fowlpox virus (FPV) (Davison et al, 2006;Johnson et al, 2010;Tong et al, 2001;Vagnozzi et al, 2012a) are commercially available. The hallmark of these recombinant vaccines is their safety, as they do not transmit from vaccinated to non-vaccinated chickens (Armour & García, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation